Development of remote operability CNC milling - ., Afzeri; Muhida, Riza; ., Darmawan (2010)
Capability of remote operation of a CNC milling machine is demonstrated. Unattended machining operation is possible to be performed by executing NC program sent from remote user. The system is designed using a computer server and connected to a PC based controlled CNC machine for real time axis monitoring remote desktop. A client accesses the machine through Internet and operate and simulate the machine activity. Operability of CNC machine supported by combination between real time virtual simulation and using remote desktop tool and Setup Free Pin type Attachment. An auto setup CNC milling machine which is equipped with specially developed Setup Free Attachment has been investigated as one solution for unattended machining process. A specially designed attachment with setup free machining methodology has been developed for horizontal machining center. Attachment consists of three main equipments; material indexing device, Sub clamp with pin and vise index